If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h = 10h + 6 Reorder the terms: 8h = 6 + 10h Solving 8h = 6 + 10h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-10h' to each side of the equation. 8h + -10h = 6 + 10h + -10h Combine like terms: 8h + -10h = -2h -2h = 6 + 10h + -10h Combine like terms: 10h + -10h = 0 -2h = 6 + 0 -2h = 6 Divide each side by '-2'. h = -3 Simplifying h = -3
| x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 | | 2x-4+x=28 | | 24=-8u+5(u+6) | | 2x^2+2y^2-2xy-2x+4y+5=0 | | 3x^2+27x-6.5=0 | | 8(x-3)+9=5x+3(-4+x) | | 15-27=2(21) | | 5w=6w+7 | | .65x+18.50=.75x+18.50 | | 5s+8t=70 | | 6x^3-x^2-27x-20=0 | | (-81)/(+9)= | | n^2+3n-12-6=0 | | 2x^2-5x^2+5x-2=0 | | 0.01x+3.97=2.04x-2.12 | | -2x+4-2x=12 | | -2b+7=11 | | n^2+7n+15-5=0 | | (3u^2)-u-10=0 | | 200-25p=0 | | x(1.8+x)=.19 | | -5(x+1)+14=-3x+1 | | 3iz-z(1+i)-4i=0 | | 9x-16-3x=26 |